2017
DOI: 10.21608/jppp.2017.46307
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Leaf Spot of Araliaceous Plants Caused by Xanthomonas campestris pv. Hederae in Egypt

Abstract: A leaf spot symptoms consentient with bacterial leaf spot disease of araliaceous plants were observed on plants of Schefflera actinophylla grown in different plots located in Cairo and Giza governorates during 2014. Eight bacterial isolates resemble Xanthomonas campestris pv. hederae obtained from symptomatic plants were characterized based on physiological and biochemical tests, pathogenicity test and Biolog microbial ID system. Furthermore, the isolates were characterized by comparing them by ERIC PCR which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…Moreover, there was a remarkable elevation of flavonoids due to the antagonistic strains in barley plants in infested and non-infested soils, and these results agree with the results of Salaheddin (2002), Salaheddin et al (2005), and Zhang et al (2001). The effectiveness of biological control achieved by the biocontrol agents of the present study showed distinctive control mechanisms that may be due to additional or synergistic effects (Zohurul et al 2003;Robe`ne-Soustrade et al 2006;Salaheddin et al 2010;Tolba 2017). The capability to produce bioactive molecules by this species of antagonistic microorganisms can trigger systemic resistance in the infected Hordeum vulgare seedlings and may be applicable than using the whole organism in future.…”
Section: Resultssupporting
confidence: 91%
“…Moreover, there was a remarkable elevation of flavonoids due to the antagonistic strains in barley plants in infested and non-infested soils, and these results agree with the results of Salaheddin (2002), Salaheddin et al (2005), and Zhang et al (2001). The effectiveness of biological control achieved by the biocontrol agents of the present study showed distinctive control mechanisms that may be due to additional or synergistic effects (Zohurul et al 2003;Robe`ne-Soustrade et al 2006;Salaheddin et al 2010;Tolba 2017). The capability to produce bioactive molecules by this species of antagonistic microorganisms can trigger systemic resistance in the infected Hordeum vulgare seedlings and may be applicable than using the whole organism in future.…”
Section: Resultssupporting
confidence: 91%